Biopsychosocial factors related to emotional disorders among adolescents - Herda, Herda; Butar Butar, Marta; Nasution, Helmi Suryani; Sitanggang, Hendra Dhermawan (JOURNAL OF Mental Health Concerns, 2026)
Background: Adolescence is a critical developmental period marked by biological, psychological, and social changes that increase vulnerability to mental-emotional disorders. Mental-emotional disorders among adolescents may impair academic performance, social relationships, and overall well-being. In Indonesia, particularly at the regional level, evidence regarding comprehensive biopsychosocial determinants among junior high school students remains limited. Purpose: To identify the biopsychosocial determinants associated with mental-emotional disorders among adolescents. Method: A cross-sectional design conducted from May to November 2025. A total of 101 students were selected using proportional stratified random sampling. Mental-emotional disorders were measured using the Strengths and Difficulties Questionnaire (SDQ). Independent variables included physical activity, sleep quality, academic burnout, smartphone addiction, peer support, bullying, parenting style, and sex. Data were analyzed using univariate and bivariate analyses with the chi-square test and prevalence ratio (PR) at a significance level of 0.05. Results: The prevalence of mental-emotional disorders among students was 41.6%. Significant associations were found between mental-emotional disorders and low physical activity (PR=2.7; 95% CI: 1.750–4.393), poor sleep quality (PR=2.4; 95% CI: 1.483–3.974), high academic burnout (PR=2.5; 95% CI: 1.604–4.162), smartphone addiction (PR=1.9; 95% CI: 1.269–3.109), low peer support (PR=1.8; 95% CI: 1.150–3.032), and experiences of bullying (PR=13.7; 95% CI: 4.558–41.760). Sex and parenting style were not significantly associated with mental-emotional disorders. Conclusion: Mental-emotional disorders among adolescents are significantly influenced by multiple biopsychosocial factors, particularly lifestyle behaviors, academic stress, peer relationships, and bullying experiences. School-based promotive and preventive interventions focusing on physical activity, sleep hygiene, stress management, strengthening peer support, and bullying prevention are strongly recommended. Keyword: Academic Burnout; Adolescents; Biopsychosocial Factors; Bullying; Mental-Emotional Disorders.